Functional outcome among patients treated by percutaneous cannulated screw with tension band for transverse patella fracture - Dhakal, Rabi Mohan; Shrestha, Rabindra Prasad; Shrestha, Bhola; Kandel, Ishwor Sharma; Acharya, Karuna; Bista, Krishna Bahadhur; Parajuli, Pravakar (Journal of Gandaki Medical College-Nepal, 2021)
Introduction:  Tension band wiring is the most commonly used treatment method for transverse patella fracture. Tension band construct can be achieved by various modifications. Percutaneous cannulated screw with tension band is a minimally invasive technique with stiffer fixation that follows tension band principle. This study aims to assess the clinical and radiological outcome using percutaneous cannulated screw with tension band for the management of transverse patella fracture.Methods: This was a prospective study among 30 adult patients who had closed displaced transverse patella fracture. Patients with polytrauma, comminuted fracture, neurovascular injury and prior injury to the limb were excluded from the study. Each patient was followed up at 2 weeks, 4 weeks, 3 months and 6 months postoperatively.Results: Among all surgically treated patients using this technique, Pain gradually decreased over time and was less than VAS score of 1 in all patients at 6 months follow-up with an average score of 0.3. The final range of motion at 6 months was: flexion ranging from 122 to 145 degrees and extension lag from  of 0 to 8 degrees. There was significant improvement in range of motion of knee in each follow up. The mean duration for fracture union was 11.4±2.3 weeks. There were no cases of nonunion and hardware failure. The mean Lyshom score was 82.5 at final follow up.Conclusions: The percutaneous fixation of transverse patella fracture with cannulated screw and SS wire is safe and effective method which gives good functional outcome.